Shir, Syrien - Bartl, Karin (e-Forschungsberichte des DAI, 2017)
The late Neolithic site of Shir is one of the few settlements of the 7th millenium BC in Syria, which was extensively investigated. The analysis of the stratigraphy of the excavations in the southern area of the site proved, for the period between c. 7000 and 6500/6400 cal BC, the existence of a a complexcommunity whose subsistence was based both on the use of wild resources of the surrounding habitats, as well as on agricultural cultivation and grazing. However, despite the seemingly favorable settlement conditions, pathological investigations of the burials of the settlement show a high infant mortality rate. Due to the favorable raw material situation in the immediate vicinity of the settlement, a household-based production of the entire range of tools and objects necessary for everyday needs can be assumed. In addition, imported raw materials and the existence of special objects testify to the site’s integration into the regional and supraregional trade networks and to craft specialization.